Gender Dynamics in Cyberlaw: Unraveling Patterns and Implications - Agustino , Anggo Dwi; Purwaningsih, Sri Budi; Nurhayati (Proceedings of The ICECRS, 2023)
This data-driven study explores the intersection of Cyber Law and gender issues by analyzing articles from Lens.org. Focusing on Law journals, it examines gender-related developments' societal implications. The study identifies leading institutions, prevalent fields, and influential authors shaping gender-focused legal discourse. Through a scatter plot, it visualizes the scholarly landscape, revealing active regions, top publishers, and journals driving crucial conversations. Key findings emphasize the synergy between law and business, essential for understanding gender narratives in Cyber Law. This research aids researchers, policymakers, and advocates in advancing gender-inclusive legal frameworks for societal progress. Highlights : Institutional Pioneers: Identifying leading institutions driving gender issues discourse in Cyber Law, essential for collaborations and knowledge exchange. Interdisciplinary Synergy: Highlighting the convergence of law and business fields in addressing gender-related challenges, emphasizing holistic solutions. Global Engagement: Mapping the active countries and regions involved in gender-focused Cyber Law research, fostering international dialogue and cooperation. Keywords: Cyber Law, Gender Issues, Legal Frameworks, Scholarly Discourse, Societal Progress